Urgency of Criminal Functionality on the Perpetrators of Santet - Kurniawan, Dedi; Anwar, Saiful (NAJAHA, 2022)
The belief in the existence of supernatural crimes is inherent in the lives of Indonesian people. The view of people who think that santet is something that can cause harm to others makes santet seen as a crime. Santet is an act of harming others using magic. This study also aims to explore criminal law for users of santet crimes. The method used in this research is normative legal research, data obtained through a literature study. The study results show that in criminal understanding, santet can be legally accounted for by reviewing articles that substantially imply regulation not only on general issues but also on uncommon issues such as santet. Sorting and clustering the substance of the santet becomes the central point so that the arguments issued can be legally accounted for; caution in understanding the sides of the importance of the santet will lead to ideas that can be justified. In the understanding of the criminal law of santet which is still difficult to accept by many people, in fact theoretically capable of being legally responsible, an open view of legal issues is the key to how the law can be fully enforced on everything that violates the rights of others, as well as on problems santet by the discussion that has been explained that in understanding the law must be open but not out of the rules of the substance of the existing article.